KEPASTIAN HUKUM PENGGUNAAN PASAL 27 AYAT (2) UU ITE DALAM PERJUDIAN ONLINE : Studi Putusan Nomor : 95/Pid.P/2021/Pn.Sby - Al-Qifari, Muh. Miqdad; Tanudjaja, Tanudjaja; Arwanto, Bambang (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2023)
Online gambling is gambling through electronic media that uses internet access as an intermediary. In this online gambling game, money is used as a bet according to the rules of the game and the number of bets is determined by the players. in principle gambling is prohibited as stipulated in article 303 of the Criminal Code, article 303 bis of the Criminal Code and the ITE Law article 27 paragraph (2). The researcher found a discrepancy in the application of the article to the Surabaya District Court decision Number: 95/Pid.B/2021/Pn.Sby in the case of online gambling crimes from this problem, so researchers can formulate this problem, namely 1.) What is the Ratio Decide in the Application of Criminal Sanctions in Verdict Number: 95/Pid.B/2021/Pn.Sby? 2.) What is the Legal Certainty on the Use of Article 27 Paragraph (2) of the ITE Law in Online Gambling Crimes in Decision Number: 95/Pid.B/2021/Pn.Sby?. the method used by researchers is a normative juridical type with a statutory approach (Statute Approach), conceptual approach (Conceptual Approach), and case approach (Case Approach). in this decision, the judge used article 303 paragraph (1) 1st of the Criminal Code, the judge should have paid attention to the provisions of the Lex Specialist Derogate Legi Generalis principle by applying article 27 paragraph (2) which regulates the crime of online gambling which is not regulated in article 303 paragraph (1) 1st Criminal Code